PENENTUAN TINGKAT PEMAHAMAN MAHASISWA TERHADAP SOCIAL DISTANCING MENGGUNAKAN ALGORITMA C4.5 - Sudipa, I Gede Iwan; I Nyoman Alit Arsana; Made Leo Radhitya (LPPM STMIK STIKOM Indonesia, 2020)
Pandemic Corona Disease 19 or called Covid19 raises a situation that requires every level of society to maintain health and perform activities work from home. One suggestion from the government is to implement social distancing for the academic community, one of which is students. However, not all students can do it due to the lack of understanding of social distancing and the demands of working status, this study seeks to measure the level of understanding of students in knowing social distancing and applying it in current conditions. Based on the questionnaire data collection distributed with the number of respondents 287 students with vulnerable ages 18-25 years later conducted a classification of datamining using the C4.5 algorithm with tree modeling, the results obtained that the accuracy of 93.73%, with class precision that is predictions of students understanding social distancing ( 96.97%), students understand but have to work (100%) and students hesitate (75.71%).